Self Efficacy, Self Esteem, Dukungan Sosial Terhadap Resiliensi Dengan Optimisme Sebagai Variabel Intervening Pada Pelaku Usaha (UMKM) Yang Terkena Pemberlakuan PPKM - Lianasari, Lianasari; Widiastuti, Hardhani; Nusandari, Arumwardhani; DC. Kuswardhani (Universitas Semarang, 2022)
AbstractThis study aims to determine the effect of self-efficacy, self-esteem and social support on resilience with optimism as a mediation (intervening) for UMKM entrepreneurs affected by the implementation of PPKM due to Covid-19. The hypothesis proposed in this study is that there is an influence between self-efficacy, self-esteem, social support on resilience and optimism is a mediation. The subjects in this study amounted to 90 subjects who were MSME entrepreneurs. The sampling technique used is non-random incidental (incidental sampling). The research data was collected using five scales, namely the resilience scale, self-efficacy scale, self-esteem scale, social support scale, optimism scale and resilience scale. Data analysis was performed using SEM-PLS analysis with WarpPLS 7.0. The results showed that self-efficacy had an effect on resilience with a correlation coefficient of 0.18 with P=0.04 (<0.05), self-efficacy had an effect on optimism with a correlation coefficient of 0.077 (P<0.01). Optimism affects resilience with a correlation coefficient of 0.59 (P< 0.01). Self esteem has no effect on resilience (P>0.44) . Social support has no effect on resilience (P>0.34) so that optimism fully mediates self-esteem and social support on resilience and optimism partially mediates self-efficacy on resilience.Keywords : self efficacy, self esteem, social support, optimisme and resilience